Herdabilidade em caracteres de crescimento de populações fragmentadas da espécie arbórea copaifera langsdorffii (fabaceae) - Kubota, Thaisa Yuriko Kuboyama [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The knowledge about the evolutionary potential of natural populations is critical to ensure the survival of the species. Heritability estimates are necessary to analyze how much of the phenotypic variation of traits are about genetic control. The aim of this study is to investigate the genetic control of growth traits in the initial phases of developing fragmented populations Copaifera langsdorffii, using microsatellite markers. Therefore, two populations of C. langsdorffii were used a municipal park located in São José do Rio Preto (SJRP) and at Assis Ecological Station (AES), both in the state of São Paulo, Brazil. The model to estimate the heritability coefficient is the method of regression of a measure of phenotypic similarity and an estimate of kinship between individuals, run the Mark programs. The coefficients of relatedness and heritability were estimated for three classes of distance (10, 20 and 30 m) within populations. Estimates of heritability were low (maximum 0.146) for all traits, ranging from positive values for regenerating individuals of the population SJRP and from negative to positive for the juvenile population AES. In evolutionary terms, these results indicate little chance of changing the population mean of the characters studied by natural selection, with the strongest environmental random effects to change this average. This result, coupled with the trend of reduction in the coefficient of heritability for height between regenerating juveniles individuals indicates also that the genetic control reduces the development of plants, in other words, natural selection in natural populations is stronger in the early stages of plant development. In short, the results suggest that there are no differences in the levels of heritability between the two populations and that the heritability for growth traits is low in both populations

O conhecimento sobre o potencial evolutivo das populações naturais é fundamental para garantir a sobrevivência das espécies. A estimativa da herdabilidade é necessária para analisar quanto da variação fenotípica de caracteres estão sobre controle genético. O objetivo desse estudo foi investigar o controle genético de caracteres de crescimento nas fases iniciais de desenvolvimento de populações fragmentadas de Copaifera langsdorffii, utilizando marcadores microssatélites. Para tanto, foram utilizadas duas populações de C. langsdorffii, uma localizada no parque municipal em São José do Rio Preto (SJRP) e uma na Estação Ecológica de Assis (EEA), ambas no Estado de São Paulo, Brasil. O modelo para estimar o coeficiente de herdabilidade consiste no método de regressão de uma medida de similaridade fenotípica e uma estimativa de parentesco entre pares de indivíduos, executado no programa Mark. Ambos coeficientes de parentesco e herdabilidade foram estimados para três classes de distância (10, 20 e 30 m) dentro das populações. As estimativas de herdabilidade foram baixas (máximo de 0,146) para todos os caracteres, variando entre valores positivos para os indivíduos regenerantes da população SJRP e entre negativos a positivos para os juvenis da população EEA. Em termos evolutivos, estes resultados indicam poucas chances de alterar a média populacional dos caracteres estudados pela seleção natural, sendo os efeitos ambientais aleatórios mais fortes para alterar esta média. Este resultado, associado à tendência observada de redução no coeficiente de herdabilidade para altura entre indivíduos regenerantes para indivíduos juvenis também indica que este controle genético reduz com o desenvolvimento das plantas, ou seja, a seleção natural em populações naturais é mais forte em fases iniciais de desenvolvimento das plantas. Em suma, os resultados sugerem que não existem diferenças nos níveis de ...
Keywords: Copaíba; Genetica florestal; Melhoramento genetico